Sodium Danshensu Cream Promotes the Healing of Pressure Ulcers in Mice through the Nrf2/HO-1 and NF-κB Pathways - Fei Yang; Cuizhen Shen (MDPI AG, 2022)
On the basis of the mice pressure ulcers (PU) model, the protective effect and potential mechanism of sodium Danshensu (SDSS) cream against PU were investigated. The mice were randomly divided into three groups: the negative control group (cream without 0.5 g SDSS), the SDSS group (cream containing 0.5 g SDSS), and the positive group (0.5 g Hirudoid®). After 7 and 14 days of ointment application, the wound-healing rate of the SDSS and positive groups was significantly higher than that of the control group (p < 0.05). The results of hematoxylin-eosin staining also indicated that SDSS has the potential to promote the healing of PU. In addition, the serum IL-6, IL-1β, TNF-α, and MDA levels decreased significantly (p < 0.01) after 14 days of SDSS treatment, while the SOD, CAT, and GSH-Px activities increased significantly (p < 0.01). In addition, SDSS cream was able to significantly increase the expression of Nrf2, HO-1, GCLM, NQO1, NF-κB p65, NF-κB p50, IKKα, and IKKβ while decreasing the expression of Keap1 and IκBαin the Nrf2/HO-1 and NF-κB pathways. Our research will provide a foundation for the future clinical prevention and treatment of PU with SDSS cream.